2006
DOI: 10.1159/000095232
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and association analysis of porcine <i>CA3</i>

Abstract: Carbonic anhydrase 3 (CA3) is a member of the carbonic anhydrase family, which plays an important role in various cell processes. In this paper, molecular characterization revealed that CA3 genomic DNA consists of seven exons and six introns, spans about 10.5 kb and maps to porcine chromosome 4q11→q14. Results of expression profiles showed that the expression levels of CA3 increased in skeletal muscles from prenatal 33- to 65-day-old Chinese Tongcheng pigs. These levels subsequently decreased to a steady state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
6
13
0
Order By: Relevance
“…In our study, the porcine CA3 gene was also differentially expressed in the skeletal muscle of Yorkshire and Meishan pig breeds. The results of expression profiles showed that the expression levels of CA3 increased in skeletal muscles from prenatal 33-to 65-day-old Chinese Tongcheng pigs and subsequently decreased to a steady state in prenatal 90-day-old, postnatal 2-day-old, postnatal 28-dayold, and pregnant 65-day-old pigs [11]. Therefore, our results are supported by these former reports.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, the porcine CA3 gene was also differentially expressed in the skeletal muscle of Yorkshire and Meishan pig breeds. The results of expression profiles showed that the expression levels of CA3 increased in skeletal muscles from prenatal 33-to 65-day-old Chinese Tongcheng pigs and subsequently decreased to a steady state in prenatal 90-day-old, postnatal 2-day-old, postnatal 28-dayold, and pregnant 65-day-old pigs [11]. Therefore, our results are supported by these former reports.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we isolated the whole genomic DNA sequence of the porcine CA3 gene and found that its structural features were identical to those reported by Wang et al [11]. Moreover, we analysed the polymorphism of microsatellites present in the whole genomic DNA sequence of CA3.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In tissues, the CO 2 transfer could also be facilitated by the presence of an intrinsic mechanism such as the enzymatic activity of carbonic anhydrase (Nomenclature of Enzyme Classification: EC 4.2.1.1. ), present in cows (Poulsen et al, 2005), pigs (Wang et al, 2006), chickens (Yoshihara et al, 1984), fish (Tohse et al, 2006) and others non-processed fresh foods…”
Section: Diffusion In Foodsmentioning
confidence: 99%
“…Kwon et al (2009) examined over two thousand reference genes to find the most stable genes between different human tissues and only 13 of all investigated genes had a low coefficient of variation (CV) and could be used as endogenous controls. Genes commonly used as endogenous controls include ACTB and GAPDH (Wang et al, 2006), but some authors have observed that they obtain poor stability results (Glare et al, 2002). Therefore, the initial aim of this study was to find the most stable endogenous controls for the analysis of gene expression in chicken muscle tissue.…”
Section: Introductionmentioning
confidence: 99%